B05 Environment-driven influences and neuroprotection in the BACHD RAT model for huntington disease. (September 2018) - Wassouf, Zinah; Hentrich, Thomas; Novati, Arianna; Riess, Olaf; Nguyen, Huu Phuc; Schulze-Hentrich, Julia M
Abstract : Background: Huntington disease (HD) is a progressive neurodegenerative disorder caused by a mutation in the huntingtin (HTT) gene. Despite being a monogenic disease, environmental factors can modulate HD phenotype. Specifically, environmental enrichment (EE) in animal models influenced markers of brain pathology, altered behavior and caused expression changes. Yet, the molecular mechanisms mediating the gene-environment interplay in the context of mHTT remain elusive. Aims: Determining preventive as well as rehabilitative effects of the EE and shedding light on the underlying molecular mechanisms as to how EE influence HD characteristics. Methods: We used the BACHD rats expressing full-length human mHTT together with wildtype littermates, and we housed the animals either in standard environment (SE) or EE, the later applied exclusively or first housed in SE until developing signs of pathology and then migrated to the EE. We assessed phenotypical, immunohistochemical responses and profiled transcriptome for changes through EE exposure. Results: Behavioral characterization together with gene expression profiles after 6 months of EE will be presented. EE prevented impairments in cognitive abilities in BACHD rats and modulated striatal gene expression. Conclusions: This initial data points towards early preventive effects from EE and modulation of the BACHD phenotype.